MALADMINISTRATION IN THE CONTEXT OF THE PUBLIC SERVICE - Sampara, Said (Journal of Humanity, 2014)
Basically every human being needs a service, even in the extreme can be said that the Ministry cannot be separated with human life. Basically every human being needs a service, even in the extreme can be said that the Ministry cannot be separated with human life Based on the purpose of organizing the public service, it can be concluded that basically the purpose of the public service, the community is satisfactory, and the satisfaction, to achieve the required quality of service excellence public services is still less give satisfaction in the community, even the often very disappointing, so sometimes the fact happens to crappy service maladministration from the implementing authorities